Differential transforms in weighted spaces - Bernardis, Ana Lucia (2006)
We extend the results by Jones and Rosenblatt about the series of the differences of differentiation operators along lacunary sequences to BMO and to the setting of weighted Lp spaces. We use a different approach which allows to establish that the one-sided Sawyer Ap weights are the natural ones to study the boundedness and convergence of that series in weighted spaces